1993
DOI: 10.1093/jac/32.3.445
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of three new fluoroquinolones and synergy with ansamycins against Mycobacterium leprae

Abstract: The efficacy of three fluorinated quinolones, clinafloxacin (PD 127391), sparfloxacin (PD 131501) and PD 131628, either alone or in combination with rifampicin/rifabutin, against Mycobacterium leprae was evaluated in vitro using two biochemical parameters to measure the metabolic activity of the organism. Clinafloxacin was found to be most effective with an MIC of 0.75 mg/L, followed by sparfloxacin (MIC 1.5 mg/L) and PD131628 (MIC 3.0 mg/L). When combined with rifampicin each of the three quinolones were addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, the antimicrobial potentiating effects of combinations of 2 and 3 with 1 were examined by FIC calculations. FIC values of Յ0.5 are considered synergistic, whereas values greater than 0.5 are considered additive (2,12,18). Based on MICs (Table 1) and FIC calculations (Table 2), the combination of compounds 1 and 2 was synergistic against A. niger, whereas the combination of compounds 1 and 3 was synergistic against M. smegmatis.…”
Section: Vol 47 2003 Synergistic Antimicrobial Activity Of Metabolimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the antimicrobial potentiating effects of combinations of 2 and 3 with 1 were examined by FIC calculations. FIC values of Յ0.5 are considered synergistic, whereas values greater than 0.5 are considered additive (2,12,18). Based on MICs (Table 1) and FIC calculations (Table 2), the combination of compounds 1 and 2 was synergistic against A. niger, whereas the combination of compounds 1 and 3 was synergistic against M. smegmatis.…”
Section: Vol 47 2003 Synergistic Antimicrobial Activity Of Metabolimentioning
confidence: 99%
“…FIC values were calculated by using the following formula: FIC ϭ (MIC Drug A in combination/MIC Drug A alone) ϩ (MIC Drug B in combination/MIC Drug B alone). Synergy was defined as an FIC value of Յ0.5, whereas FIC values between 0.5 to 1.0 were considered to be the result of additive antimicrobial effects (2,12,18).…”
mentioning
confidence: 99%
“…Furthermore, synergism was observed when levofloxacin was combined with either rifabutin or KRM-1648 but not when it was combined with rifampin. The superiority of rifabutin and KRM-1648 over rifampin against M. leprae has been shown earlier (6,7). However, at this stage we cannot explain why levofloxacin exhibits synergism with rifabutin and KRM-1648 but not with rifampin.…”
mentioning
confidence: 69%
“…Recently, we have also observed parallelism between the ATP levels, [ 3 H]thymidine uptake values, microscopic counts, and phenolic glycolipid (PGL-1) levels of M. leprae cells incubated in DH medium. Using this system, we have evaluated the antileprosy activities of several compounds, and the in vitro susceptibility results were confirmed by the established mouse footpad system (5)(6)(7)(8). On the basis of these results, it is safe to suggest that the increase in metabolic activity of M. leprae observed in the present studies is an indication of the increase in cell numbers in primary cultures, as seen in control cultures to which no drugs were added.…”
mentioning
confidence: 99%
“…This suggests the bactericidal activity of VUF-8514 on M leprae. On the other hand, VUF-8842 had no inhibitory effect on the metabolic activity of M leprae even at 0.32 ,ug/ml-the highest concentration tested to compare against rifampin, whose MIC against M leprae has been shown to be 0.3 ,ug/ml (10). In subsequent studies, no growth inhibition of M keprae was observed even when the concentration of VUF-8842 in the DH medium was raised up to 2.56 ,ug/ml.…”
mentioning
confidence: 90%